(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This paper analyzes the way in which our legal system can solve the problems caused by the COVID-19 pandemic in legal relations under private law. In addition, it aims to verify the importance of the basic principles of contract law to alleviate the effects caused by the current public health crisis and comment on the impacts of federal laws n. 13.874/19 (Economic Freedom Law) and n. 14.010 /2020 in contractual relations. It is concluded that, in Law, no single rule will be able to solve the problems caused by the pandemic. Thus, it is essential to have a singular look at each concrete case. For the development of this article, the literature review methods were used together with the hypothetical deductive method, performing a legal analysis of the assertions described.